Phytoplankton carbon to chlorophyll a model development: a review - Gui, Jiang; Sun, Jun (Frontiers in Marine Science, 2024)
The cellular carbon content and chlorophyll a (Chl a) concentration are two of the most significant indices for assessing phytoplankton biomass. Recording and monitoring these biomasses are essential tasks in phytoplankton research, and the carbon-to-chlorophyll a (C:Chl a) ratio serves as a crucial conversion tool between them. Although the C:Chl a ratio varies widely, it is influenced by external environmental factors, making modeling studies of C:Chl a particularly important.This paper provides an overview of the historical development of the C:Chl a model, beginning with early empirical models and progressing to the development of mechanistic models. This discussion is followed by an examination of existing gaps and future challenges in current C:Chl a modeling, particularly the potential underestimation of carbon biomass in existing C:Chl a models for dinoflagellates exhibiting multiple growth strategies. Finally, it is suggested that future C:Chl a models should strive to achieve a balance between reliability and applicability.